Heat and mass transfer analysis of unsteady hybrid nanofluid flow over a stretching sheet with thermal radiation - Sreedevi, P.; Sudarsana Reddy, P.; Chamkha, Ali (SN applied sciences, 2020)
Unsteady magneto-hydrodynamic heat and mass transfer analysis of hybrid nanofluid flow over stretching surface with chemical reaction, suction, slip effects and thermal radiation is analyzed in this problem. Combination of carbon nanotubes and silver nanoparticles are taken as hybrid nanoparticles and water is considered as base fluid. Using similarity transformation method, the governing equations are changed into system of ordinary differential equations. These equations together with boundary conditions are numerically evaluated by using finite-element method. The influence of various pertinent parameters on the profiles of fluids concentration, temperature, and velocity is calculated and the outcomes are plotted through graphs. The values of non-dimensional rates of heat transfer, mass transfer and velocity are also analyzed, and the results are depicted in tables. Temperature sketches of hybrid nanofluid intensified in both steady and unsteady cases as volume fraction of both nanoparticles rises.